DISCUSSIONS ON A CASE OF MINOR ERYTHEMA MULTIFORME BULLOSUM AT A CHILD - Luminița Lazăr; Janine Lazăr; Roxana Popescu (Amaltea Medical Publishing House, 2008)
The authors present the case of a little girl aged 5 years and 6 months presenting a minor erythema multiforme bullosum. The diagnosis was established on clinical criteria (erytemato - papulous, vesiculobullous tegument lesions resulting from the expose of the skin with apparition of liquid when exfoliating the papules) at a child with a good general condition. It was established a possible etiology due to a staphylococcus evidentiating the existence of the staphylococcus aureus in the gathering of papules liquid. It was discussion about the differential diagnosis of the bullous dermatitis. Unlike simple cases with autolimitative evolution, when the treatment is useless, the respective case had a particularly prolonged evolution and required a general and local treatment.